Short-Acting Oral Nifedipine versus Intravenous Labetalol for the Control of Severe Hypertension in the Postpartum Period: A Retrospective Cohort Study - Booker, Whitney A.; Bejerano, Shai; Frappaolo, Anna; Miller, Eliza C.; Bello, Natalie A. (American Journal of Perinatology, 2024)
This study aimed to compare the effectiveness of oral short-acting (SA) nifedipine with intravenous (IV) labetalol for the treatment of postpartum (PP) severe hypertension.We conducted a retrospective cohort study of women who delivered at a tertiary care facility between January and December 2018, had not previously received antihypertensive medication, and required treatment for PP severe hypertension defined as systolic blood pressure (SBP) ≥ 160 mm Hg and/or diastolic blood pressure (DBP) ≥110 mm Hg. Exposure groups were defined by the receipt of either oral SA nifedipine or IV labetalol. The primary outcome was time (minutes) to BP control (SBP < 160 mm Hg and DBP <110 mm Hg). Secondary outcomes included number of doses required to achieve BP control, crossover to the alternative medication, and recurrence of severe range BP after the achievement of BP control. t-Tests and Wilcoxon–Mann–Whitney tests were used to analyze continuous variables and chi-square tests or Fisher's exact tests were used to analyze categorical variables. Multivariable linear regression models were conducted for the primary outcome, controlling for potential confounders in a sequential fashion across three models. A Kaplan–Meier plot was also created.Of the 99 women included, 74 received oral SA nifedipine and 25 received IV labetalol. There was no significant difference in minutes to initial BP control between groups (30.5 minutes [interquartile range, IQR: 20.0–45.0] vs. 25.0 minutes [IQR: 14.0–50.0]; p = 0.82) or in the rate of recurrent severe BP. However, patients who received nifedipine required fewer doses to achieve control (p < 0.01) and did not require crossover (0 vs. 12%, p = 0.01).Both oral SA nifedipine and IV labetalol are effective options for treating PP severe hypertension. An initial choice of nifedipine was associated with a lower requirement for subsequent doses of medication and no need for crossover to an alternative antihypertensive medication.
Keywords: blood pressure; postpartum; severe hypertension; nifedipine; labetalol